Estimation of the influence of exogenous factors on the vitamin D deficiency in pregnant women in Saint Petersburg - E L Khazova; N Yu Yakovleva; E N Belyaeva (IP Berlin A.V., 2017)
Vitamin D is a precursor of calcitriol, a secosteroid hormone regulating calcium-phosphorus metabolism and a wide range of proliferative and immune responses. Solar UV radiation (290-315 nm) is an initiator of vitamin D production in the human skin. In the northern latitudes, the amount of such radiation reaching the earth's surface is less than in the southern ones, which can be the reason for the wide spread of vitamin D deficiency in the North-West region. Hypovitaminosis takes on particular urgency in women during the pregravid period and during pregnancy, therefore the study of this issue is extremely topical. Materials and methods. The study involved 178 women in the first trimester of pregnancy. The concentration of calcifediol was determined and anthropometric examination was performed. The calendar month of inclusion in the study was taken into account. Women are divided into 2 groups: Group 1 (n = 65) women with a calcifediol level above 30 ng/ml, group 2 (n=113) - below 30 ng/ml. Results. In both groups, the average concentrations of calcifediol were lower in winter. The total variability of the values of calcifediol is not due to the trend, but due to the seasonal component. The seasonal difference of calcifediol fluctuates above and below zero on the graph of the seasonal component, with the "summer vitamin D" season comprising the months from June to September, and the "winter vitamin D" season from October to May. In this period is necessary the exogenous introduction of cholecalciferol or additional irradiation of the skin with UV radiation.